Impacts of Fire in Social Wasps Community in an Area of Regenerating Brazilian Savanna - Clemente, M. A. [UNESP]; Ceridorio, H. F.; Mendes, D. R. S. [UNESP]; Guevara, R.; Silveira, O. T.; Giannotti, E. [UNESP]; Moleiro, H. R. [UNESP]; Vieira, K. M. (Univ Estadual Feira Santana, 2019)
Fire is one of the most common natural harassments and it is characterized as an important component of the systems, although little studied regarding the influence of this event in social wasps communities. One month after the end of the collections, the area of Regenerating Brazilian Savanna of the present study undertook a fire in exactly half of the points sampled, which motivated one further year of sampling. The aim of this study was to compare the social wasps fauna collected before and after the fire, indicating a possible impact on their populations. In the first year of collection, before the fire, 21 species (seven genera) were sampled with a total amount of 297 individuals. In the second year, after the fire, 14 species were collected (reduction of 33,33% in richness) and six genera, with an abundance of 153 wasp individuals of Vespidae (loss of 48,48% of individuals). The area 1 in the first year, presented an abundance of 182 individuals (61,27%) and 16 species (76,19%) and the area 2, 115 (38,73%) and 19 species (90,47%). For the area 1 in the second year, 74 individuals (48,36%) and 12 species (85,71%) were captured and for the area 2 there were 79 individuals (51,64%) distributed among nine species (64,28%). However, we did not find significant values for both the abundance and for the richness among the areas and the years of sampling. Nine species were not registered in the second year, although two presented their registration only after the fire.
Keywords: Inventory; Polistinae; conservation; richness